High rates of multidrug-resistance in Enterococcus spp. isolated from dogs and cats in Lima, Perú - Castro Pérez, Verónica Karen (2021)
Enterococcus spp. are opportunistic pathogens which can rapidly acquire antimicrobial resistance causing septicemia, endocarditis or nosocomial infections in humans and animals. The purpose of this study was to identify and determine the antimicrobial susceptibility of enterococci isolated from dogs and cats which were examined in veterinarian clinics in Lima, Perú during 2019-2020. A total of 125 grampositive catalase negative cocci were isolated from urine, skin, ear, oral, abdominal, pharyngeal and abscess samples. Antimicrobial susceptibility was tested by the disk diffusion method. Inhibition zone diameters were interpreted according to the Clinical Laboratories Standards Institute (CLSI), breakpoints (CLSI, 2018) and, when breakpoints were unavailable for bacteria of animal origin, according to the human CLSI breakpoints (CLSI, 2021).